Peran Media Massa Surat Kabar terhadap Pengaruh The Beatles dalam Perkembangan Musik Indonesia Tahun 1970–2000 - Siti Nur Aulia; Mahbub Hefdzil Akbar; Fathia Lestari (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the strategic role of newspapers in introducing and reinforcing the influence of The Beatles on the development of popular music in Indonesia from 1970 to 2000. Utilizing a historical research method with a descriptive-analytical approach, the study underwent four main stages: heuristics, involving the collection of primary sources such as newspaper archives from Kompas, Bali Post, and What’s On; source criticism for data validation; interpretation to analyze data correlations; and historiography to synthesize a systematic historical narrative. Additionally, the study employs Antonio Gramsci’s theoretical framework of hegemony to dissect how mass media functions as a cultural production tool that builds "spontaneous consent" within society regarding Western musical influences. The results indicate that prior to the rise of the internet, newspapers through intensive entertainment columns successfully represented The Beatles not just as a musical group, but as a symbol of modernity, global creativity, and the pinnacle of modern musical aesthetics. Mass media acted as an agent of cultural change, shifting the perception of Indonesian society from viewing Western music as a moral threat to seeing it as a standard of cultural progress. The impact of this coverage is evident in the modernization of local musicians' musicality, the adoption of electric instruments, and the emergence of tribute band phenomena like the Bharata Band, which preserved the collective memory of the public. In conclusion, newspapers acted as cultural curators that strategically shaped national tastes and facilitated the process of cultural hybridization, where local and global elements converged to create a modern Indonesian musical identity that remains rooted in local values.